Familial risk of early and late onset cancer: nationwide prospective cohort study. (20th December 2012) - Kharazmi, E; Fallah, M; Sundquist, K; Hemminki, K
Abstract : Objective To determine whether familial risk of cancer is limited to early onset cases. Design Nationwide prospective cohort study. Setting Nationwide Swedish Family-Cancer Database. Participants All Swedes born after 1931 and their biological parents, totalling >12.2 million individuals, including >1.1 million cases of first primary cancer. Main outcome measures Familial risks of the concordant cancers by age at diagnosis. Results The highest familial risk was seen for offspring whose parents were diagnosed at an early age. Familial risks were significantly increased for colorectal, lung, breast, prostate, and urinary bladder cancer and melanoma, skin squamous cell carcinoma, and non-Hodgkin's lymphoma, even when parents were diagnosed at age 70-79 or 80-89. When parents were diagnosed at more advanced ages (≥90), the risk of concordant cancer in offspring was still significantly increased for skin squamous cell carcinoma (hazard ratio 1.9, 95% confidence interval 1.4 to 2.7), colorectal (1.6, 1.2 to 2.0), breast (1.3, 1.0 to 1.6), and prostate cancer (1.3, 1.1 to 1.6). For offspring with a cancer diagnosed at ages 60-76 whose parents were affected at age <50, familial risks were not significantly increased for nearly all cancers. Conclusion Though the highest familial risks of cancer are seen in offspring whose parents received a diagnosis of a concordant cancer at earlier ages, increased risks exist even in cancers of advanced ages. Familial cancers might not be early onset in people whose family members were affected at older ages and so familial cancers might have distinct early and late onset components.